Zoonosis: An Emerging Link to Antibiotic Resistance Under “One Health Approach” - Dafale, Nishant A.; Srivastava, Shweta; Purohit, Hemant J. (Indian journal of microbiology, 2020)
Current scenario in communicable diseases has generated new era that identifies the “One health” approach to understand the sharing and management of etiological agents with its impact on ecosystem. Under this context the relevance of zoonotic diseases generates major concern. The indiscriminate and higher use of antibiotics in animal husbandry creates substantial pressure on the gut microbiome for development of resistance due to shorter generation time and high density. Thus, gut works as a bioreactor for the breeding of ARBs in this scenario and are continuously released in different niches. These ARBs transfer resistance genes among native flora through horizontal gene transfer events, vectors and quorum sensing. About 60% of infectious diseases in human are caused by zoonotic pathogens have potential to carry ARGs which could be transmitted to humans. The well documented zoonotic diseases are anthrax cause by Bacillus anthracis , bovine tuberculosis by Mycobacterium tuberculosis , brucellosis by Brucella abortus , and hemorrhagic colitis by Escherichia coli . Similarly, most of the antibiotics are not completely metabolized and released in unmetabolized forms which enters the food chain and affect various ecological niches through bioaccumulation. The persistence period of antibiotics ranges from < 1 to 3466 days in environment. The consequences of misusing the antibiotic in livestock and their fate in various ecological niches have been discussed in this review. Further the light sheds on antibiotics persistence and it biodegradation through different abiotic and biotic approaches in environment. The knowledge on personnel hygiene and strong surveillance system for zoonotic disease including ARBs transmission, prevention and control measures should be established to regulate the spread of AMR in the environment and subsequently to the human being through a food web.